Healthcare utilisation and costs in the diagnosis and treatment of progressive-fibrosing interstitial lung diseases - Holtze, Colin; Flaherty, Kevin; Kreuter, Michael; Luppi, Fabrizio; Moua, Teng; Vancheri, Carlo; Scholand, Mary B. (European respiratory review, 2018)
There are over 200 interstitial lung diseases (ILDs). In addition to patients with idiopathic pulmonary fibrosis (IPF), a percentage of patients with other ILDs also develop progressive fibrosis of the lung during their disease course. Patients with progressive-fibrosing ILDs may show limited response to immunomodulatory therapy, worsening symptoms and lung function and, ultimately, early mortality. There are few data for ILDs that may present a progressive fibrosing phenotype specifically, but we believe the burden and healthcare costs associated with these conditions may be comparable to those reported in IPF. This review discusses the burden of ILDs that may present a progressive fibrosing phenotype and the factors impacting healthcare utilisation. - Tweetable abstract ERSpublications - click to tweetData for ILDs with a progressive fibrosing phenotype are lacking, but the burden and healthcare costs associated with these conditions may be comparable to those reported in IPF http://ow.ly/Eoht30mS4Nx
Gesehen am 19.11.2019